Justice in the Republic of Poland: Problems in Implementing the Principle of Independence of the Judiciary - Balicki, Ryszard; Juškevičiūtė-Vilienė, Agnė (Teisė, 2021)
The right-wing populist Law and Justice party , which came to power in 2015 in Poland, sought not only to implement its conservative and Christian ideas through the executive and the legislative powers, but also to influence the justice. This article presents an analysis of legal acts adopted or amended on the initiative of this ruling party, which shows how the judicial power has been systematically usurped by this political party, in spite of the constitutional principle of the separation of powers, and states that the principle of judicial independence has been violated.